2014
DOI: 10.1098/rsta.2013.0086
|View full text |Cite
|
Sign up to set email alerts
|

Disentangling degenerate solutions from primary transit and secondary eclipse spectroscopy of exoplanets

Abstract: Infrared transmission and emission spectroscopy of exoplanets, recorded from primary transit and secondary eclipse measurements, indicate the presence of the most abundant carbon and oxygen molecular species (H 2 O, CH 4 , CO and CO 2 ) in a few exoplanets. However, efforts to constrain the molecular abundances to within several orders of magnitude are thwarted by the broad range of degenerate solutions that fit the data. Here, we explore,… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
89
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 85 publications
(99 citation statements)
references
References 62 publications
8
89
2
Order By: Relevance
“…The total column abundance and deflection experienced by a ray is twice that quantity since the rays goes through these layers twice: once moving downward, and once moving upward through the atmosphere. Although the computational grid used in Bétrémieux & Kaltenegger (2013, 2014 was composed of 0.1 km-thick layers, we have found that the precision of the computations improves significantly when the thickness of the computational layers decreases (see section 4.1), and that the desired thickness depends on the atmospheric scale height. Hence, we now adjust this parameter as required by the atmosphere for which we do the computations.…”
Section: Ray-tracing Algorithmmentioning
confidence: 99%
See 4 more Smart Citations
“…The total column abundance and deflection experienced by a ray is twice that quantity since the rays goes through these layers twice: once moving downward, and once moving upward through the atmosphere. Although the computational grid used in Bétrémieux & Kaltenegger (2013, 2014 was composed of 0.1 km-thick layers, we have found that the precision of the computations improves significantly when the thickness of the computational layers decreases (see section 4.1), and that the desired thickness depends on the atmospheric scale height. Hence, we now adjust this parameter as required by the atmosphere for which we do the computations.…”
Section: Ray-tracing Algorithmmentioning
confidence: 99%
“…This expression for the column abundance has been previously derived in terms of these modified Bessel functions (see e.g. Griffith 2014). However, this is only the leading term in our Taylor series, and corresponds to the non-refractive case.…”
Section: Taylor-series Expansion Of Integrandsmentioning
confidence: 99%
See 3 more Smart Citations